Resilience of the poorest: coping strategies and indigenous knowledge of living with the floods in Northern Namibia - Hooli Lauri. (Springer Link, 2022)
In Northern Namibia, the climate is highly polarised between dry and wet seasons, and local communities have lived with these varying weather extremes for centuries. However, the recent changes in socio-environmental dynamics—associated with urbanisation, inappropriate spatial planning, and population growth—have disturbed the river system in the area. These changes, together with torrential seasonal rains, have aggravated the social impacts of the flood events. By using various qualitative and quantitative data sources, and comparative analyses between the flood dynamics in urban and rural environments, this research studies local residents’ coping strategies to endure the irregular flood events from the perspective of socio-ecological resilience. Particular interest is placed on the learning processes that enhance the residents’ capability to cope and the role of indigenous knowledge. Indigenous knowledge (IK) has been emphasised as a source of resilience in both theory and practice, as it is built upon learning from past experiences of natural hazards. The findings reveal that the floods are a result of complex and relational development without the necessary linear relationship between the causes and effects. The abrupt socio-ecological changes, together with the multiple stressors related to poverty, have made residents more vulnerable to the flood events and attenuated the communities’ coping strategies based on IK. Instead of focusing on the communities’ capacity to self-organise, the focus of resilience building needs to be directed to emphasising the broader socio-political processes, which are making the communities vulnerable in the first place.